2006
DOI: 10.1186/1477-7800-3-33
|View full text |Cite
|
Sign up to set email alerts
|

Secondary penile tumours revisited

Abstract: ObjectiveTo highlight the salient features of metastatic malignancies involving the penis, with special reference to the primary tumour sites, metastatic mechanisms, clinical features, differential diagnosis, treatment and prognosis.MethodsA comprehensive search of the literature was performed using MEDLINE and EMBASE, using the keywords 'penis', 'secondary malignancy', 'metastasis' and 'malignant priapism' to identify reviews and case reports of secondary penile malignancy. A case of rare clinical presentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
142
0
14

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(159 citation statements)
references
References 16 publications
(42 reference statements)
3
142
0
14
Order By: Relevance
“…Various mechanisms for penile metastasis have been suggested, which include retrograde venous spread, retrograde lymphatic spread, arterial spread, direct extension, implantation and secondary to instrumentation. 9 Accumulating clinical evidence indicates that retrograde venous spread from the pudendal into the dorsal venous system of the penis is the most likely mechanism. About two-thirds of all penile metastasis are detected at a mean time of 18 months after the detection of the primary tumour; the remaining third present at the same time as the primary tumour.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various mechanisms for penile metastasis have been suggested, which include retrograde venous spread, retrograde lymphatic spread, arterial spread, direct extension, implantation and secondary to instrumentation. 9 Accumulating clinical evidence indicates that retrograde venous spread from the pudendal into the dorsal venous system of the penis is the most likely mechanism. About two-thirds of all penile metastasis are detected at a mean time of 18 months after the detection of the primary tumour; the remaining third present at the same time as the primary tumour.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3]9,16 More than 80% of patients die within 6 months, irrespective of the primary tumour and treatment. 16 However, in our case, the imaging studies did not show other metastases; therefore, we concluded that the penis was the isolated metastatic site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It accounts for less than 1% of cancers in men in the U.S. The incidence of disease is more common in South America, Southeast Asia, and parts of Africa.1 In the U.S., it is estimated that only 1820 new cases of penile cancer will be diagnosed in 2015.2 Metastatic involvement of the penis is a rare disease, 3,4 with approximately 480 reported cases. …”
mentioning
confidence: 99%
“…[6][7][8] The prognosis for these patients is very poor, as it typically indicates widespread metastatic disease. 4,5,9 We present the first case of penile metastasis from primary transitional cell carcinoma (TCC) of the bladder that spares the urethra. …”
mentioning
confidence: 99%